The making of a counter-culture icon : Henry Miller's Dostoevsky - Bloshteyn, Maria R., 1971- (University of Toronto Press, 2007)
The Making of a Counter-Culture Icon gives invaluable insight into the early careers of the Villa Seurat writers and testifies to Dostoevsky's influence on twentieth-century literature.